Evaluation The Characteristics Of Soil Chemical Properties Of Oil Palm In The Adolina Plantantion Ptpn Iv Serdang Bedagai On Several Generation Of Planting - Nuraini Nuraini; Abdul Rauf; Jamilah Jamilah (Universitas Sumatera Utara, 2018)
ABSTRACT The reseach aimed to determine changes in the characteristics of some soil chemical properties planted with oil palm in several generations of planting. This research was conducted in July 2016 until January 2017, using survey method with descriptive analysis. Soil samples were taken in 3 generations of planting, G0 (land never planted with oil palm), G1 (land cultivated by oil palms for 11 years), G3 (land cultivated by oil palms for 58 years) and G4 (land Which has been cultivated for oil palm plantations for 72 years). That Generation II land is still projected at the time of this research. In each generation three soil profiles are made, then tested by t Test. The results showed that the increase of planting generation to change the soil characteristics of soil chemistry is very apparent in the decreasing soil pH which is more acid, while the C-Organic, total of N, total of P, total of K and soil carbon stocks different is not real meaning that the generation of planting in oil palm plants does not affect the soil chemical properties in the Adolina plantation. But increasing the value of CEC land the longer the generation of planting. Keywords: generation of planting, oil palm, soil chemical properties